2007
DOI: 10.1523/jneurosci.0059-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine Dithiocarbamate Activates Akt and Improves Spatial Learning in APP/PS1 Mice without Affecting β-Amyloid Burden

Abstract: Pyrrolidine dithiocarbamate (PDTC) is a clinically tolerated inhibitor of nuclear factor-B (NF-B), antioxidant and antiinflammatory agent, which provides protection in brain ischemia models. In neonatal hypoxia-ischemia model, PDTC activates Akt and reduces activation of glycogen synthase kinase 3␤ (GSK-3␤). Because chronic inflammation, oxidative stress, and increased GSK-3␤ activity are features of Alzheimer's disease (AD) pathology, we tested whether PDTC reduces brain pathology and improves cognitive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 82 publications
11
110
0
1
Order By: Relevance
“…Administration of minocycline, an anti-inflammatory drug, did not change the levels of total, soluble, or insoluble Ab, while ameliorating behavioral deficits in transgenic mice (Fan et al 2007). Similarly, treatment with dithiocarbamates, which can inhibit the preinflammatory agent NFkB, also improved AD pathology without affecting Ab burden (Malm et al 2007). In addition to anti-inflammatory treatments, the cholesterol-lowering drug simvastatin induced cognitive improvement without changing levels of Ab in transgenic mice (Li et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Administration of minocycline, an anti-inflammatory drug, did not change the levels of total, soluble, or insoluble Ab, while ameliorating behavioral deficits in transgenic mice (Fan et al 2007). Similarly, treatment with dithiocarbamates, which can inhibit the preinflammatory agent NFkB, also improved AD pathology without affecting Ab burden (Malm et al 2007). In addition to anti-inflammatory treatments, the cholesterol-lowering drug simvastatin induced cognitive improvement without changing levels of Ab in transgenic mice (Li et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Here, in Tg2576 mice treated with 4-PBA, we found that memory deficits were markedly ameliorated without any alteration in cortical Ab levels and senile plaques, suggesting that 4-PBA does not interfere with Ab production to produce its beneficial effects on learning and memory. Earlier studies have shown that improved learning and memory performance is not always associated with any detectable alteration in brain Ab burden (Dodart et al, 2002;Gong et al, 2004;Malm et al, 2007, Green et al, 2008, suggesting that the relationship between soluble and insoluble brain Ab concentrations and memory impairment in transgenic mice is task specific and complex. In addition, in extensive studies, no clear correlation between deposited forms of Ab (such as plaques) and memory impairment in AD patients has been shown (Hyman et al, 1984;Braak and Braak, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PBT2 and clioquinol both provided promising cognition outcomes in clinical trials (11,16). In a related study, AD mice were treated for 7 months with the metal-ligating compound pyrrolidine dithiocarbamate (PDTC), and the treatment was shown to induce phosphorylation of Akt and GSK3␤, decrease tau phosphorylation, and improve cognitive performance of the mice (35). Surprisingly, however, PDTC did not change A␤ levels as determined by ELISA.…”
Section: Discussionmentioning
confidence: 99%